The Effect of Ethanol Extract of Tamarillo (Solanum betaceum) on Superoxide Dismutase Expression in Mouse (Mus musculus) Lungs after Lead Acetate Exposure - Karina Putri Dianita; Herley Windo Setiawan; Nurmawati Fatimah; Reny I'tishom; Mohammad Subkhan (Majalah Biomorfologi, 2026)
Background: Lead (Pb), a toxic heavy metal that does not break down in the environment, seriously endangers human health. Oral exposure to lead affects the lungs, causing disrupted physiological functions and respiratory disorders, including chronic obstructive pulmonary disease (COPD). Reactive oxygen species (ROS) are produced following lead exposure, reducing endogenous antioxidants, particularly superoxide dismutase (SOD). Administration of exogenous antioxidants to enhance SOD activity is therefore a crucial preventive strategy. Objective: To examine the effect of tamarillo (Solanum betaceum) ethanol extract on SOD expression in the lungs of mice (Mus musculus) after lead acetate exposure. Materials and Methods: The authors used twenty-five mouse lung tissue samples. Each treatment group comprised five samples: C0 (negative control, given only distillated water), C1 (positive control, given lead acetate at a dose of 0.075 g/kg BW), T1 (lead acetate + tamarillo extract at concentration of 100 mg/kg BW), T2 (lead acetate + tamarillo extract 200 mg/kg BW), and T3 (lead acetate + tamarillo extract 400 mg/kg BW). The duration of the treatments was 35 days. Results: After administering 0.075 g/kg BW of lead acetate, the study found a substantial increase in SOD expression (p < 0.05). In addition, compared to the positive control group, the administration of 100 mg/kg BW of tamarillo ethanol extract resulted in a significant increase in SOD expression (p < 0.05). Conclusion: Ethanol extract of tamarillo, particularly at a level of 100 mg/kg BW, efficiently increases SOD expression in mouse lungs.